2018
DOI: 10.1038/s41467-018-03358-x
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylic acid-modified metal oxide catalyst for selectivity-tunable aerobic ammoxidation

Abstract: Controlling the reaction selectivity of a heterobifunctional molecule is a fundamental challenge in many catalytic processes. Recent efforts to design chemoselective catalysts have focused on modifying the surface of metal nanoparticle materials having tunable properties. However, precise control over the surface properties of base-metal oxide catalysts remains a challenge. Here, we show that green modification of the surface with carboxylates can be used to tune the ammoxidation selectivity toward the desired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 53 publications
2
60
0
Order By: Relevance
“…As shown in Table 1, using well-crystallized MnO 2 catalysts, a near quantitative conversions were observed, and the yields of nitrile ( 3a ) varied from 24.6% to 58.9%, with 24.1–61.9% yield of imine ( 2a ) formed (Table 1, entries 1–4). In comparison, amorphous MnO x has much increased specific surface area and mass-specific activity (Supplementary Table 1) 23 , affording a complete conversion of amine and 86.5% yield of nitrile ( 3a ) (Table 1, entry 5). The time course of the synthesis of 3a over amorphous MnO x displays a steep volcano curves for 2a , indicating that the imine of 2a is the reaction intermediate and could be hardly obtained in high selectivity via tuning of the reaction time (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 1, using well-crystallized MnO 2 catalysts, a near quantitative conversions were observed, and the yields of nitrile ( 3a ) varied from 24.6% to 58.9%, with 24.1–61.9% yield of imine ( 2a ) formed (Table 1, entries 1–4). In comparison, amorphous MnO x has much increased specific surface area and mass-specific activity (Supplementary Table 1) 23 , affording a complete conversion of amine and 86.5% yield of nitrile ( 3a ) (Table 1, entry 5). The time course of the synthesis of 3a over amorphous MnO x displays a steep volcano curves for 2a , indicating that the imine of 2a is the reaction intermediate and could be hardly obtained in high selectivity via tuning of the reaction time (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MnO x was prepared according to the literature procedure 23 . A 100 mL aqueous solution containing 40 mmol KMnO 4 was added into another 250 mL solution of EtOH-H 2 O (5:1) containing 40 mmol MnAc 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inspired by manganese-oxide catalysts with high activity towards oxidation reactions [19][20][21][22] , and encouraged by our recent investigations on preparing heterogeneous manganese catalysts for alcohol oxidation reactions [23,24] . Herein, we use commercial MnCO 3 as the precursor to prepare manganese oxides by simply pyrolyzing it at 400°C under an air atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, our laboratory has been engaged in research of construction of functional catalytic materials and production of chemicals from biomass‐based feedstocks via catalytic methods . We found that both basic sites (pyridinic N‐doped carbon species in CoO x ‐N/C) and basic supports (MgO and Mg(OH) 2 ) could contribute to high catalytic performances in oxidation or oxidative esterification.…”
Section: Introductionmentioning
confidence: 99%